(untitled) (Innovaciones Educativas, 2019)
The objective of the article is to describe the importance of Information and Communication Technologies (ICT) as support tools in the III Cycle and Diversified Vocational Cycle services of Costa Rica, for the establishment of accessible environments that promote the integral development of the population. The bibliographic review methodology of documents related to the use of ICT in the teaching and learning processes, autonomy, disability and educational supports was implemented; the collaborative work was used to establish selection criteria such as the time space margin, specific terminologies and area of specialization. As a result of this, results are derived about ICT as educational supports in the services of III Cycle and Vocational Diversified Cycle; as well as its role for the promotion of autonomy and the considerations to be assumed when designing educational material for people with intellectual disabilities.